Strategi Pembelajaran Pendidikan Agama Islam Dan Budi Pekerti Bagi Siswa Slow Learner Di SMP Negeri 2 Baturraden Kabupaten Banyumas - Eka Hidayah, Tiarany; Chaqil Harimi, Abdal (Jurnal Pendidikan Agama Islam, 2025)
This study aims to explore effective Islamic Religious Education (PAI) and Character Building learning strategies for slow learner students in grade VII at SMP Negeri 2 Baturraden. Slow learner students have below average academic achievement and require more intensive time and practice to master the material. The importance of PAI and Character Building for slow learner students is emphasized as a guide to life. With the aim of knowing the process of implementing PAI learning for slow learner students in the school. The results of the study concluded that the PAI and Character Building learning strategies for slow learner students in grade VII at SMP Negeri 2 Baturraden were designed by considering the diversity of student characteristics. PAI and Character Building teachers implemented Cooperative Learning strategies and personal or individual approaches as the main approaches. Cooperative Learning allows students to learn in groups, help each other, and share understanding, while Active Learning strategies actively involve students in learning activities such as discussions, questions and answers, simulations, and direct practice. The combination of these two strategies has proven effective in creating an adaptive, meaningful, and empowering Islamic Education (PAI) learning process for all students, especially slow learners, so that they not only understand the material but also experience improvements in social, emotional, and spiritual aspects